2020
DOI: 10.26714/lensa.10.2.2020.263-279
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Student’s English Dialogue Anxiety in Online Learning through Board Game

Abstract: The COVID 19 has been going on since April 2020 in Indonesia. It has resulted in the Indonesian government, especially the Ministry of Education and Culture, taking preventive steps to minimize contracting the virus. One of them is using online learning for students to go to school. However, there are challenges for teachers and students while learning in an online class, such as students who are often absent, students will quickly feel bored, students tend to be passive in the learning process, students do no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
(13 reference statements)
1
5
0
Order By: Relevance
“…The experiment showed that it was found that the proposed anxiety coping strategies, such as differentiating, proficiency level, and individualized approaches to learning, lead to a decrease in anxiety and an increase in academic performance. The relationship between decreased anxiety and increased achievement found during the experiment echoes the findings of other empirical studies [6], [11], [25]. The researchers established a link between task simplification and high verbal association learning outcomes in anxious children.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The experiment showed that it was found that the proposed anxiety coping strategies, such as differentiating, proficiency level, and individualized approaches to learning, lead to a decrease in anxiety and an increase in academic performance. The relationship between decreased anxiety and increased achievement found during the experiment echoes the findings of other empirical studies [6], [11], [25]. The researchers established a link between task simplification and high verbal association learning outcomes in anxious children.…”
Section: Discussionsupporting
confidence: 82%
“…These works emphasize that anxiety in online learning has its unique features associated with several common fears: i) Technology fear (worry about hardware malfunction, connection breakdown, or software disruption); ii) Uncertainty about one's digital literacy and related competencies; iii) Lack of personal connection with other students and with the teacher; and iv) Distractions by electronic entertainment. A few researchers had suggested using gaming content and learning approaches to engage student attention in remote learning environments, which proved to be successful [23], [25].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, through board games, pupils were able to speak fluently [15,17,31,43,[46][47][48]52] and make less grammatical errors in their speech [15,17,43,44,[47][48][49]52,54,56]. In addition to this, board games exposed pupils to a myriad of speaking opportunities in different speaking contexts [7,45,46,51,53,54] and motivated pupils to speak [7,17,46,48,50,51,53,56].…”
Section: Authors Exposure Motivation Pronunciation Fluency Grammarmentioning
confidence: 99%
“…Board games were regarded as tools that exposed pupils to various chances to practice speaking the target language naturally. Pupils were connected to real-life situations that provided meaningful learning opportunities through board games [45,53], thus stimulating them to develop their creativity and thinking into a wider area [46]. Pictures and words provided on the cards in board games enabled pupils to develop ideas for their speech content and pupils gained experience using the language naturally for their daily communication [7].…”
Section: Authors Exposure Motivation Pronunciation Fluency Grammarmentioning
confidence: 99%
“…Also, Nuzulia and Catur. K [13] added that games could be applied in online learning and gave significant effect to lessen students' anxiety in speaking performance. This implies how principle is speaking activity.…”
Section: Introductionmentioning
confidence: 99%